Re: What's wrong with this assuming?

*To*: mathgroup at smc.vnet.net*Subject*: [mg111113] Re: What's wrong with this assuming?*From*: Bob Hanlon <hanlonr at cox.net>*Date*: Tue, 20 Jul 2010 07:55:43 -0400 (EDT)*Reply-to*: hanlonr at cox.net

Use the assumption directly in Simplify or FullSimplify Simplify[(x^2 + x)^2 + h, x^2 + x == h] h (h+1) FullSimplify[(x^2 + x)^2 + h, x^2 + x == h] h (h+1) Or put Simplify or FullSimplify within the scope of the Assuming construct Assuming[x^2 + x == h, Simplify[(x^2 + x)^2 + h]] h (h+1) Assuming[x^2 + x == h, FullSimplify[(x^2 + x)^2 + h]] h (h+1) Bob Hanlon ---- Sam Takoy <sam.takoy at yahoo.com> wrote: ============= Hi, I have a situation where I have to simplify an expression that contains x and h, but x is given implicitly by h, so I can't explicitly eliminate it. So here's a simpler example that I'm trying and it does nothing: Assuming[x^2 + x == h, (x^2 + x)^2+h] // FullSimplify Is there a way to make this work? Thanks! -- Bob Hanlon